Potential nutrient release from rock based minerals ameliorants (rock flours) in gold mine rehabilitation - Keulder, C.J. (North-West University (South Africa), 2020)
Gold mines produce significant volumes of waste material in the form of tailings and waste rock during their life cycle. A large ecological footprint is therefore created that needs to be rehabilitated. Rehabilitation planning can be extensive and a large volume of topsoil is required to function as a growth medium. To reduce the volume of topsoil required, an alternative is to use the waste material (waste rock) as a resource to minimize rehabilitation expenses. The use of rock-based ameliorants, also known as rock flour, has been successfully tested in both agriculture and environmental applications for rehabilitation and nutrient availability. Previous studies done on this subject indicates that rock powder could provide the essential nutrients to plants during the rehabilitation process to promote plant growth. In this study, three common igneous rocks, namely granite, gabbro and andesite, were used as a finely ground rock-based ameliorant for rehabilitation. The seed of Cynodon dactylon (Couch grass) was sown into pots to provide an incubation cover and test the vitality of the plant after chemical and physical alteration of the material during the experiment. Three concentrations of granite, gabbro, and andesite were mixed with gold tailings as a growth medium. Due to the low pH value of the gold tailings material, lime was added to half of the samples to test the impact of liming in conjunction with rock flour. Vegetation surveys included the monitoring of the germination potential of the C. dactylon seed, the dry weight and nutrient absorption potential of C. dactylon in the different mediums and changes in the chemical and physical soil parameters over time. The results indicated that andesite rock flour was the most effective ameliorant to be used for rehabilitation of gold mine tailings. However, if a growth medium has high saline conditions, a mixture of andesite and granite ameliorants would provide the best chance of success to rehabilitate a gold mine tailings storage facility (TSF). By using these ameliorants, the footprint created by gold mines as well as the rehabilitation costs can be reduced.
MSc (Environmental Sciences), North-West University, Potchefstroom Campus